2011
DOI: 10.1111/j.1538-7836.2010.04138.x
|View full text |Cite
|
Sign up to set email alerts
|

A role for Rab10 in von Willebrand factor release discovered by an AP‐1 interactor screen in C. elegans

Abstract: Summary. Background: Endothelial von Willebrand factor (VWF) mediates platelet adhesion and acts as a protective chaperone to clotting factor VIII. Rapid release of highly multimerized VWF is particularly effective in promoting hemostasis. To produce this protein, an elaborate biogenesis is required, culminating at the trans-Golgi network (TGN) in storage within secretory granules called Weibel-Palade bodies (WPB). Failure to correctly form these organelles can lead to uncontrolled secretion of low-molecular-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…An RNAi screen in C. elegans for defective transport vesicle adaptor complex 1 component AP-1 showed that rab-10 is important for von Willebrand factor secretion [52]. Here we present the first in vivo studies in a multicellular model organism showing that exoc-7 and exoc-8 are functionally linked to the small GTPase rab-10 .…”
Section: Discussionmentioning
confidence: 80%
“…An RNAi screen in C. elegans for defective transport vesicle adaptor complex 1 component AP-1 showed that rab-10 is important for von Willebrand factor secretion [52]. Here we present the first in vivo studies in a multicellular model organism showing that exoc-7 and exoc-8 are functionally linked to the small GTPase rab-10 .…”
Section: Discussionmentioning
confidence: 80%
“…Because Slp4-a can also bind Rab8 and Rab3A-3D 15,21 (and supplemental Figure 4A), we next looked for the expression and WPB localization of these Rab proteins. Although HUVECs express Rab8, 11,29 we detected neither endogenous nor epitope-tagged Rab8 …”
Section: Slp4-a Is Localized To Wpbsmentioning
confidence: 72%
“…Studies in the C. elegans intestine show a crucial function for Rab11 and the clathrin adaptor AP1 in promoting apical polarization (Michaux et al 2011;Shafaq-Zadah et al 2012). AP1 is specifically required for the formation of apical Rab11 vesicles and for the apical localization of Cdc42 and the polarity determinant PAR-6, similar to their role in MDCK cell polarization.…”
Section: Transcytosis and Apical Lumen Morphogenesis In Polarized Epimentioning
confidence: 95%